Centrifugation. Issue 9 (28th October 2014) - Gallagher, Sean R.
Abstract: Centrifugation is a ubiquitous technique in the life science laboratory that uses specialized equipment (centrifuges) to spin, or centrifuge, samples in rotors, generating centrifugal force for a range of applications that include pelleting of precipitates, isolating organelles, and protein and DNA purification. The unit describes basic applications, definitions, and references, and provides up‐to‐date tables for rotor specifications from major suppliers. © 2014 by John Wiley & Sons, Inc.